The Care of Vulnerability: The Proposal of an Ethical Space - Alfano, Linda; Fontana, Paolo; Ciliberti, Rosagemma (Medicina Historica, 2023)
In recent years, the category of vulnerability has increasingly become the subject of attention from ethical, legal, and political reflections. Various events have shown how vulnerability cannot be considered a specific attribute of some individuals or certain segments of the population but belongs to all living beings by virtue of the deep interconnection between human beings and the ecosystem. This need for a relationship with others is precisely what has prompted a revision both of our concept of social responsibility, and of the taking care of the needs of the Other, within a holistic "One Health" vision based on the recognition that human, animal, and ecosystem health are all indissolubly linked. Even in the medical and health care field has emerged a new relational dimension based on the recognition of the constant precariousness of the health-disease balance and the awareness of the connections between the person and the space they inhabit. And it is precisely thanks to this new approach that the homo independens, called to self-affirmation and total autonomy, has given way to the homo curans who, aware of the network of relationships they are part of, reaches out to others, towards an increasing valorization of a generative dimension of solidarity. For this purpose, the authors analyze the proposal put forward by the National Bioethics Committee (NBC) to implement in Italy the so-called "Ethical Space": a place capable of offering the listening an welcoming of diverse life experiences in a protected relational context, free from the different dynamics of power and subjection, and capable of welcoming the discussion on ethical issues regarding health, giving voice both to health professionals and individual citizens and associations that represent them.